From magma to macrophage: the grand challenges of volcanic environments - Catherine A. Mériaux; Edward Ntim Gasu; Guillaume Nyagatare; Vicky Ruganzu; Philbert Ntivuguruzwa; Mwumvaneza Mutagoma; Atalay Ayele; Julyan H. E. Cartwright; Valérie Cayol; Laurent Charlet; Claudia Corradino; Antonio Costa; et al. (Bulletin of Volcanology, 2026)
The interdisciplinary study of volcanic processes, which extend across all timescales and lengths, requires a multitude of approaches, ranging from analogue and numerical modelling to observations and fieldwork and extending to mathematics. A conference was held at the East African Institute for Fundamental Research, affiliated with the University of Rwanda, a country which, along with the Democratic Republic of Congo, presents a unique geodynamic context. Located along the East African Rift, an active seismic region, Rwanda is close to two of Africa's most active volcanoes, including Nyiragongo, which overlooks Lake Kivu, a deep volcanic lake rich in dissolved carbon dioxide and methane, the latter of which is used for electricity generation. In this context, the conference addressed many “classic” volcanological topics and their modern advances, such as multiphase lava flows, subsurface magma propagation, seismic and deformation signals from a volcano, modelling of volcanic emission dispersion, and volcanic lakes. Yet, it broadened the discussion to the volcanic particle-water interface and its impact on soils, volcanoes and climate change, and volcanoes and health. This article aims to highlight and share the richness of the integration and interconnectedness of the various questions related to a volcanic environment, as well as their impact on society. Ultimately, this conference also demonstrated the importance of promoting science in Africa and developing countries so that the next generation of African researchers is equipped to address the challenges facing their nations.

Clover in vineyards, a potential trap plant for the mealybug Pseudococcus calceolariae—a vector of GLRaV-3 to grapevines but not clover species - Rebecca Gough; Kar Mun Chooi; Manoharie Sandanayaka; Vicky Davis; Duncan Hedderley; Tara Taylor; Daniel Cohen; Cecilia A. Prator; Rodrigo P. P. Almeida; Vaughn A. Bell; Robin M. MacDiarmid (Journal of Pest Science, 2025)
Grapevine leafroll disease (GLD) affects grapevines worldwide. The primary causal agent of GLD is grapevine leafroll-associated virus 3 (GLRaV-3), which spreads to uninfected grapevines via mealybugs and soft-scale insects. Pseudococcus calceolariae (Hemiptera: Pseudococcidae) is a mealybug vector of GLRaV-3 in New Zealand. P. calceolariae also colonizes clovers ( Trifolium spp.) growing naturally as vineyard ground cover. Separating mealybug from GLRaV-3 grapevine host could be enhanced by a trap plant: an alternative host attractive to and retentive of the target pest. We evaluated the association between P. calceolariae and ‘Grasslands Huia’ white clover (GHWC). GHWC seed was sown under grapevines in a commercial vineyard (14 × 0.4 ha plots); the control was under-vine herbicide use (7 × 0.4 ha plots, where only few Trifolium spp. plants grew). After 2 years, GHWC cover peaked at 40% mealybug infestation in 2019. From 2018 to 2021, P. calceolariae detection and abundance on GHWC was significantly higher than plants from the control plots. There was no treatment effect for mealybug infestation of grapevine leaves nor of GLRaV-3 incidence, independent of vintage. A glasshouse trial found no transmission of GLRaV-3 by P. calceolariae to any of 256 plants among five clover cultivars tested ( Trifolium spp.), including GHWC; mealybug transmitted GLRaV-3 to 35 of 107 Nicotiana benthamiana plants. The results showed that in the 5-year period, added GHWC did not decouple P. calceolariae from the grapevine to reduce GLRaV-3 incidence, but rapid colonization of GHWC by mealybug and the lack of GLRaV-3 transmission to GHWC are encouraging. Further evaluation is needed to assess whether plant biodiversity can benefit a GLRaV-3 ecological management objective.

Experimental assessment of the biosafety of Trissolcus japonicus in New Zealand, prior to the anticipated arrival of the invasive pest Halyomorpha halys - J. G. Charles; G. A. Avila; Kim A. Hoelmer; Sophie Hunt; Robin Gardner-Gee; Frances MacDonald; Vicky Davis (BioControl, 2019)

Establishment and seasonal activity in New Zealand of Mastrus ridens, a gregarious ectoparasitoid of codling moth Cydia pomonella - John G. Charles; W. R. Manoharie Sandanayaka; James T. S. Walker; Peter W. Shaw; Asha Chhagan; Lyn M. Cole; Kate Colhoun; Vicky A. Davis; D. Roger Wallis (BioControl, 2019)